Sarcopenia Induced by Chronic Liver Disease in Mice Requires the Expression of the Bile Acids Membrane Receptor tgr5 - Gonzalez-Rojas, A; Cabello-Verrugio, C; Abrigo, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Sarcopenia is a condition of muscle dysfunction, commonly associated with chronic liver disease (CLD), characterized by a decline in muscle strength, the activation of the ubiquitin-proteasome system (UPS), and oxidative stress. We recently described a murine model of CLD-induced sarcopenia by intake of hepatotoxin 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC), which presents an increase in plasma bile acids (BA). BA induced skeletal muscle atrophy through a mechanism dependent on the Takeda G protein-coupled receptor 5 (TGR5) receptor. In the present study, we evaluated the role of TGR5 signaling in the development of sarcopenia using a model of DDC-induced CLD in C57BL6 wild-type (WT) mice and mice deficient in TGR5 expression (TGR5−/− mice). The results indicate that the decline in muscle function and contractibility induced by the DDC diet is dependent on TGR5 expression. TGR5 dependence was also observed for the decrease in fiber diameter and sarcomeric proteins, as well as for the fast-to-slow shift in muscle fiber type. UPS overactivation, indicated by increased atrogin-1/MAFbx (atrogin-1) and muscle RING-finger protein-1 (MuRF-1) protein levels and oxidative stress, was abolished in tibialis anterior muscles from TGR5−/− mice. Our results collectively suggest that all sarcopenia features induced by the DDC-supplemented diet in mice are dependent on TGR5 receptor expression. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.